2021
DOI: 10.1097/olq.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High-Risk Human Papillomavirus by RNA Assay in Home Self-Collected Samples Among Underscreened People in North Carolina

Abstract: Background: Low-income and uninsured people with a cervix (PWC) are at the highest risk of being underscreened for cervical cancer. We evaluated the prevalence of high-risk human papillomavirus (hrHPV) on home self-collected samples, as well as rates of in-clinic follow-up and risk factors associated with hrHPV positivity in this at-risk population.Methods: My Body My Test 3 was conducted between 2016 and 2019 in North Carolina among individuals aged 25 to 64 years, overdue for cervical cancer screening, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Eligible individuals were aged 25–64 years, were not pregnant, had an intact cervix (ie, no history of hysterectomy), had an income of 250% or less of the US Federal Poverty Level, were uninsured or enrolled in Medicaid or Medicare, and were living within the catchment area of a trial-associated clinic and eligible to receive screening from a trial-associated clinic. 13 , 17 The US Census Bureau sets annual household income thresholds, which vary by family size and composition, to define who is living in federal poverty. 18 Additionally, women were eligible only if they self-reported not having a Papanicolaou test for 4 years or more or not having a physician-collected HPV test in 6 years or more, which is considered overdue for screening according to US guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligible individuals were aged 25–64 years, were not pregnant, had an intact cervix (ie, no history of hysterectomy), had an income of 250% or less of the US Federal Poverty Level, were uninsured or enrolled in Medicaid or Medicare, and were living within the catchment area of a trial-associated clinic and eligible to receive screening from a trial-associated clinic. 13 , 17 The US Census Bureau sets annual household income thresholds, which vary by family size and composition, to define who is living in federal poverty. 18 Additionally, women were eligible only if they self-reported not having a Papanicolaou test for 4 years or more or not having a physician-collected HPV test in 6 years or more, which is considered overdue for screening according to US guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…18 Additionally, women were eligible only if they self-reported not having a Papanicolaou test for 4 years or more or not having a physician-collected HPV test in 6 years or more, which is considered overdue for screening according to US guidelines. 2 , 13 , 17 If the participant was an established patient at one of the trial-affiliated clinics, the date of their last cervical cancer screening was confirmed by use of the participant’s medical records at the time of appointment scheduling. Trial eligibility was assessed by use of a telephone questionnaire administered by trial staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 759 women were eligible for baseline analyses as described elsewhere [33]. Of these 759 eligible participants, one participant did not self-identify any race or ethnicity, and 48 selfidentified as a race or ethnicity other than White, Black, or Hispanic/Latina.…”
Section: Data Analysesmentioning
confidence: 99%
“…Most surveyed women intended to get a Pap test in the next six months (70.6%). Our multivariable model (Table 3) indicated that older women were less likely to intend to screen compared to women ages 25 [25][26][27][28][29][30][31][32][33][34]. Black women were more likely to intend to screen compared to White women (OR: 1.48 (1.02, 2.06)).…”
Section: Intention To Screenmentioning
confidence: 99%